Direct-write assembly of 3D scaffolds using colloidal calcium phosphates inks - Richard,Raquel C. (2014)
Additive manufacture techniques using concentrated colloidal inks are a promising approach for creating three-dimensional (3D) calcium phosphates scaffolds for bone repair and regeneration. Among those, the direct-write assembly allows building scaffolds with precise size and geometry. In the present work, commercial β-TCP and HA were used to produce two types of colloidal ink. According to the ink composition used to build the scaffolds, two different groups were obtained. Group I: scaffolds produced with β-TCP-based ink; and Group II: scaffolds produced with biphasic CaP-based ink (BCP). The 3D scaffolds were assembled in a cylindrical shape (Φ = 8mm x H= 16 mm) with interconnected pore channels of approximately 500μm by robotic deposition of 64 layers using a robocasting machine. The mechanical compression property of the scaffolds was determined using universal testing machine. To assure the controlled geometry of the scaffolds, digital images were obtained by reconstructing each individual scan obtained with a micro-computed tomography. An optical contact angle measurement system was used to evaluate the wettability of the materials. After analyzing the results it was concluded that: the robocasting system is suitable for building 3D periodic calcium phosphates scaffolds; the direct-write assembly didn't change the hydrophilic characteristic of CaPs; and presented mean compressive strength around 11 MPa (β-TCP group) and 15 MPa (BCP group), which is compatible with trabecular bone.